The determinants of crop productivity and its effect on food and nutrition security in rural communities of South Africa - Hlatshwayo, Simphiwe Innocentia; Ngidi, Mjabuliseni Simon Cloapas; Ojo, Temitope Oluwaseun; Modi, Albert Thembinkosi; Mabhaudhi, Tafadzwanashe; Slotow, Rob (Frontiers in Sustainable Food Systems, 2023)
High crop productivity has a potential to improve food and nutrition security status of smallholder farmers. However, smallholder farmers operate in a dynamic environment whereby their crop production is affected by various factors that hinder it from lessen food insecurity and malnutrition in rural areas. The study attempted to investigate the impact of crop productivity on household food and nutrition security status in South Africa. The quantitative research method was used to collect the secondary data. A stratified random sampling technique was employed to select a total of 1520 participants. Out of the 386 crop producers, 176 were from Mpumalanga and 210 were from Limpopo. The descriptive results showed that most of smallholder farmers do not have access to irrigation system, mechanization and agricultural inputs. The Household Food Insecurity Access Scale showed that most smallholder farmers (43%) in Mpumalanga were mild food insecure, while in Limpopo 37% were moderately food insecure. The results from House Dietary Diversity Score (HDDS) showed that in the overall sampled population, 57% of smallholder farmers consumed highly diverse diets (> 6 food groups) whereas 25% and 18% of smallholder farmers consumed medium dietary diversity (4 – 5 food groups) and low diverse diets (< 3 food groups), respectively. Irrigation system and involvement in crop production had positive influence on crop productivity of smallholder farmers. The results from CMP model showed that livestock ownership, harvest and disability in the family had a negative impact on food security of smallholder farmers. While household size had a positive impact on food security of smallholder farmers. The results also showed that social grant, agricultural assistance and harvest had a negative impact on nutrition status of smallholder farmers. While household size had a positive impact on nutrition status of smallholder farmers. In light to these results, it was the recommended that smallholder farmers need to be trained on how to use resources that they have efficiently in order to increase their crop productivity It was also recommended that there are more workshops and trainings that need to be conducted in rural areas to increase awareness in food and nutrition security.